INSTITUTION EFFICIENCY VERSUS THE LEVEL OF DEVELOPMENT OF LOCAL GOVERNMENTS (A STUDY AT THE LEVEL OF POLAND’S REGIONAL DIVISION) - Magdalena Wojarska; Karolina Babuchowska; Wiesława Lizińska; Renata Marks-Bielska (Acta Scientiarum Polonorum. Oeconomia, 2018)
As the socio-economic reality is growing increasingly complex, the role of local governments in the management of events and processes occurring in local communities gains importance. Considering the fact that the basic task of local authorities is to stimulate the growth and development of a given local entity, an analysis was undertaken to the aim of assessing the relationship between the level of local development and the institutional efficiency of local self-governments and vice versa, in a regional approach (NUTS 2). To achieve this aim, mixed data were analysed, that is raw data (acquired via survey from 1,220 municipalities) and secondary data (from the database of the Local Data Bank). The efficiency of local governments was measured with an aggregate factor EFF, while the level of development was assessed with the DEV measure. The results indicate that the local governments did rather poorly in terms of both efficiency and development. In both cases, the mean value of the applied synthetic measures reached no more than 30% of the maximum attainable score. The basic tools in the research were correlation and regression analysis. Both procedures demonstrated the presence of a relationship between the two analysed categories (r = 0.365). Moreover, the analysis of regression showed that the impact of developmental processes on the improvement of efficiency of local governments was stronger that the influence of improved efficiency on developmental processes occurring in the analysed municipalities.